URBAN SPRAWL OF THE CITY OF YOGYAKARTA,SPECIAL REFERENCE TO THE STAGEOF SPATIAL TRANSFORMATION (Case Study at Maguwoharjo Village, Sleman District) - Sri Rum Giyarsih (Indonesian Journal of Geography, 2010)
The study was conducted in Maguwoharjo Village, Depok Sub-District,Sleman District, which is part of urban fringe area experiencing regionaltransformation. This study aims at understanding the regional transformationstages in the location studied. The survey method using in-depth interviews withsome informants was implemented. The data analysis was done descriptivequalitatively. From this study, it is found out that spatial distribution of regionaltransformation stages is closely associated with street connection and growthareas. Some areas directly bordering on Yogyakarta-Surakarta roads have higherregional transformation intensity than villages distant from the streets and growthareas.